How do people learn to use spreadsheets? (Work in progress) - Sarkar, Advait; Gordon, Andy (Psychology of Programming Interest Group (PPIG), 2018)
How can we help users discover and learn spreadsheet features? In this work-in-progress report, we present findings from semi-structured interviews with seven participants, which asked questions on the themes of learning and adopting spreadsheet features. We find that feature adoption in spreadsheets is informal, opportunistic, and social. There appear to be three components to feature adoption: discovery,expertise acquisition, and attention investment. Users fall on a spectrum of intrinsic motivation for learning. We close with a few reflections on how features might be designed with adoption in mind.